If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 26 = r * 13 Reorder the terms for easier multiplication: 26 = 13r Solving 26 = 13r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-13r' to each side of the equation. 26 + -13r = 13r + -13r Combine like terms: 13r + -13r = 0 26 + -13r = 0 Add '-26' to each side of the equation. 26 + -26 + -13r = 0 + -26 Combine like terms: 26 + -26 = 0 0 + -13r = 0 + -26 -13r = 0 + -26 Combine like terms: 0 + -26 = -26 -13r = -26 Divide each side by '-13'. r = 2 Simplifying r = 2
| x+10x+4=180 | | 4x+1+5-2x+3x=2x-5+x | | 15=t^2+2t | | 8x-12=-5x+27 | | 7y+4y-8=80 | | -5x+1=y | | .2x+.3(x+1)=2 | | 6x^2-2=-50 | | y[n]+0.4y[n-1]=3x[n] | | (X-11)(7x+1)=0 | | 3+30x=15x+30 | | 6x+3y=9fory | | 1/5x-3=-6 | | Ln(3x-2)=10 | | 14A+13B-6A+7= | | 10=12-8 | | 4+4=-6 | | y=3-1/2x | | 5(a-1)-4(a-2)=2(5a+20) | | 10=2x-86 | | F(9)=3 | | 1000=r^3/2 | | 3(X+2X)+9R= | | 20y+3x=50 | | ((3y+4)*2)+((y+3)*2)=70 | | .5n+15=3n | | (X+5)(x+5)-49=0 | | -12=w+18 | | 5z-18-z+2= | | 10=(2*6)-8 | | 2x-3x-10=-9 | | B-2b=b+4b+2 |